Phenotypic characterisation of peripheral blood lymphoid cells in people exposed to fibrous zeolite. Issue 12 (December 1986) - Ozesmi, M; Karlsson-Parra, A; Hillerdal, G; Forsum, U
Abstract : Among inhabitants of the village of Karain in Turkey there is an extremely high incidence of malignant mesothelioma, most probably due to exposure to erionite, which is a fibrous zeolite and similar in appearance and properties to asbestos. This mineral may be found in the dust in the village. To characterise possible disturbances in the immune system of people exposed to fibrous zeolite, a phenotypic characterisation of lymphoid cells in the peripheral blood of 74 immigrants to Sweden from Karain was performed. Compared with normal controls, the mean percentages of Leu 4+ cells (Pan-T) and Leu 3a+ cells ("helper/inducer" T cells) were significantly decreased, whereas the mean percentage of Leu 2a+ cells ("suppressor/cytotoxic" T cells) was normal, leading to a significant reduction of the Leu 3a/Leu 2a subset ratio. The percentage of B cells (Leu 12+ cells) was significantly increased, whereas the percentages of both HLA-DR+ and HLA-DQ+ cells were normal. The percentage of natural killer cells (NK) and killer (K) cells as defined by the monoclonal anti-Leu 7 and anti-Leu 11b were also normal. These findings indicate that exposure to fibrous zeolite causes a numerical imbalance between the two phenotypically different T cell subsets similar to that seen in asbestos exposed individuals.